(3TQM efgGL GdHjVGhis - (3GdGSfhi (B/ (3YHO GdQMje Hf MSfs; (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi egO CUhd TQjYJg HcJGHg GdbOje GdGRdi hHYO aEf CUhd GdabO Yde YXe bOQg hJHjf TQag EP gh bGYOI GdCMcGe GdTQYjI s
(3BNQgG (B:s
(3hPcQ GHf GdUdGM CjVkG eG MGUdg Efg jJYjf JbdjO GdGFeI GdGQHYI Ohf ZjQge dCf ePGgH GdGQHYI bO GfJTQJ Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B298s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1879s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs